PENGETAHUAN KEUANGAN DI KALANGAN MAHASISWA - Kusumadyahdewi, Kusumadyahdewi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
Currently, variety of banking products to facilitate customer transactions. So it is important to know about the knowledge of finance, including financial products. This research measures the student's understanding on financial knowledge consists of knowledge of personal finance, savings and loans, insurance, investment. The student has followed the course of accounting and financial management largely discusses financial firms, but researchers always explains its application to personal finances when teaching the subject. Measurement of the level of knowledge using questionnaires, then measured using the percentage of correct answers. Knowledge of personal financial management has been good, while knowledge of savings and loans, insurance, investments are at a low level. This study has shown the importance of improving the material being taught on the subject to expand the application on personal financial management, and understanding of banking products, insurance and investment, because students will also go to the public where it will be related to its financial problems. so hopefully with his knowledge of finance can finish well. Keywords: personal finance management